Two new species of Eucosmini from the Bahamas (Lepidoptera: Tortricidae) - Gilligan, Todd M.; Matthews, Deborah L.; Miller, Jacqueline Y. (Zootaxa, 2018)
Recent surveys to document the poorly known moth fauna of the Bahamas have resulted in the collection of more than 60 morphospecies of Tortricidae. Among these are several Eucosmini, including undescribed representatives of Eucosma and Pelochrista that are similar to several species present in the southeastern United States. Eucosma bahamae, sp.n., a member of the E. refusana group, and Pelochrista wrighti, sp.n., a member of the P. canana group, are described and illustrated.